Carl Ransom Rogersâ Theory in Paragraph Writing Class - Farikah, Farikah; Yuwono, A. (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
This paper aims at describing the model of teaching paragraph writing based on Carl Ransom Rogersâ theory. Carl Ransom Rogers is one of the leading figures of humanist learning theory. Based on this theory, the learning process is to help learners to be able to achieve their self-realization in accordance with the basic skills and uniqueness of the learners. The significance of the learner (significant learning) is very influential on the learning process. It occurs when learning is felt relevant to the needs and goals of the students. Related to the enactment of the President of the Republic of Indonesia number 87 of 2017 on September 6, 2017 on Strengthening Character Education (Penguatan Pendidikan Karakter), abbreviated as PPK, it is necessary to develop the models of teaching and learning of paragraph writing that can integrate the skills of writing and character education. It proved that implementing models of teaching paragraph writing through Question and Answer, Humanistic, Creative Problem Solving, Demonstration, Discussion, and Grouping Model supports the establishment of communication and personal relationships between persons and individuals, groups within the school community. It means that through those models, the learners can acquire the knowledge of writing and character education as well.